Inventarisasi Arthropoda Predator, Agens Pengendali Serangga Spodoptera frugiperda (Lepidoptera: Noctuidae) pada Pertanaman Jagung (Zea mays) - Sarah Cahyani Ahmad; Della Aprilia; Dhanillo Djulian; Hana Elja Azzahra; Karina Ayuningtias; Putri Azzahra Lutfiah; Arsi Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Ahmad SC, Aprilia D, Djulian D, Azzahra HE, Ayuningtias K, Azzahra LP, Arsi A. 2021. Inventory of predatory arthropods in controlling Spodoptera Frugiperda (Lepidoptera: Noctuidae) insects in maize crops (Zea mays). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 329-337. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Maize is a plant that contains high carbohydrates and is one of the staple foods after rice. At the beginning of 2019, corn farmers in Indonesia had to face a new problem, namely the reduction of maize yields due to the attack of the Spodoptera frugiperda pest. S. frugiperda attack cause economic losses. In this case, proper control is needed so that these pests will not cause massive losses. One of them is controlled by using predatory arthropods. For this reason, it is necessary to carry out an inventory of predatory arthropods in corn plantations. This paper aimed to identified predatory arthropod species to controlled S. frugiperda pests in maize plantations. The methodology was carried out by literature review of journals and related articles. The predator found in the maize crop were from the Formicidae family. The species found were Camponatus sp, Camponatus sericeus, Pheidole sp, Oecophylla langinoda, Branchyponnera sennaarenis, megaponera sp, Pheidole megachepala. Other arthropods spesies found were Chrysoperla externa, Ceraeochrysa cubana, Pheidole megacephala (Hymenoptera: Formicidae), Haematochares obscuripennis, and Peprius nodulipes (Hemiptera: Reduviidae). Thus, the amount of spesies have been found were 3 species of predatory arthropods from the order Neuroptera, 1 species from the order Mantodea, 3 species from the order Dermaptera, 10 species from the order Hymenoptera, 3 species from the order Coleoptera, 1 species from the order Hemiptera, 1 species from the order Diptera and 2 species have been found. of the order Araneae.